2018
DOI: 10.1186/s12887-018-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional profiles of children with cerebral palsy in Jordan based on the association between gross motor function and manual ability

Abstract: BackgroundCerebral palsy (CP) is the most common cause of physical disability in childhood. A major challenge for delivering effective services for children with CP is the heterogeneity of the medical condition. Categorizing children into homogeneous groups based on functional profiles is expected to improve service planning. The aims of this study were to (1) to describe functional profiles of children with CP based on the Gross Motor Function Classification System-Expanded & Revised (GMFCS-E & R) and the Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(31 reference statements)
1
7
0
2
Order By: Relevance
“…Consistent with other research 43 44 cerebral palsy was the most common reported childhood diagnosis in this study. Cerebral palsy is a syndrome accompanied by movement disorders resulting from permanent damage to the developing brain which impairs mobility.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other research 43 44 cerebral palsy was the most common reported childhood diagnosis in this study. Cerebral palsy is a syndrome accompanied by movement disorders resulting from permanent damage to the developing brain which impairs mobility.…”
Section: Discussionsupporting
confidence: 93%
“…The 32 included studies were published between 1984 and 2020. Most of the studies were from Saudi Arabia ( n = 10) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Jordan ( n = 8) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], Egypt ( n = 6) [ 47 , 48 , 49 , 50 , 51 , 52 ], and Iraq ( n = 4) [ 53 , 54 , 55 , 56 ]. Other studies were from Sudan ( n = 2) [ 57 , 58 ], Libya ( n = 1) [ 59 ], and Palestine ( n = 1) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were a variety of study designs. Most were of case-series ( n = 13) [ 32 , 33 , 34 , 36 , 38 , 40 , 41 , 42 , 43 , 44 , 53 , 55 , 56 ] and cross-sectional design ( n = 11) [ 29 , 31 , 39 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Other study designs included: case-control ( n = 5) [ 35 , 54 , 58 , 59 , 60 ], retrospective review ( n = 2) [ 37 , 57 ], and prospective/retrospective cohort ( n = 1) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And in practical settings, things may either improve or deteriorate with aging in such cases. 2 Cerebral palsy is a prevalent neurological problem in infants, occurring around 2-2.5 out of every 1000 live births globally 3 .…”
Section: Introductionmentioning
confidence: 99%